Verbal advertising neologisms from a multimodal perspective: word, image and common ground - Barrajón López, Elisa (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Despite the close relationship between neology and advertising, since both try to surprise the interlocutor, there are still few works that highlight lexical creation as an advertising tool. Our objective is to provide new data on this field of study through the analysis of six advertisements that contain verbal neologisms in imperative. Given the heterogeneity of this type of discourse, we take as starting point a multimodal perspective that examines how the visual and textual code interact in the interpretation of the message that the advertiser tries to communicate. The word-image thus becomes a discursive strategy conditioned, fundamentally, by the common ground that the speaker wants to exploit (broad or restricted). Therefore, with the analysis carried out, we specify in each case what is the semantic relationship between the image and the word, on the one hand, and, on the other, what level of common ground (specialized or general) the advertiser applies.
Keywords: Neological verbs; multimodality; image-word; common ground